Proceedings Issue No. 1 - 2nd Arctic Ungulate Conference - Haugerud (ed.), Rolf Egil (Rangifer, 1996)
The 2nd International Arctic Ungulate Conference was held 13-17 August 1995 on the University of Alaska Fairbanks campus. The Institute of Arctic Biology and the Alaska Cooperative Fish and Wildlife Research Unit were responsible for organizing the conference with assistance from biologists with state and federal agencies and commercial organizations. David R. Klein was chair of the conference organizing committee. Over 200 people attended the conference, coming from 10 different countries. The United States, Canada, and Norway had the largest representation. The conference included invited lectures; panel discussions, and about 125 contributed papers.